Distinct virome compositions and lack of viral diversification indicate that viral spillover is a dead-end between the western honey bee and the common eastern bumblebee - Dean A. McKeown; Elaine Evans; Jessica Helgen; Jenny Warner; Rishia Zimmern; Rebecca Masterman; Adrienne Berrington; Morgan Nemecek; Clara Costello; Elise Bernstein; Poppy J. Hesketh-Best; Bridget Mendel; et al. (Communications Biology, 2025)
Abstract Pathogen spillover events are of global concern as they have the potential to cause significant harm to the novel host species. The potential of viral spillover from the western honey bee (Apis mellifera) to other insects is well established. New variants should inevitably emerge following a host expansion, yet to our knowledge no study has shown this within this system. To investigate the outcome of viral spillover, we sequenced the RNA biased viromes of sympatric A. mellifera (n = 389) and common eastern bumblebee Bombus impatiens (n = 117) over three years. Distinct viromes occurred within each bee species throughout the study duration, with only one of the well-characterized honey bee viruses, sacbrood virus, consistently found in the bumblebee virome. Viruses shared by both bees shared over 98% nucleotide identity, and no bumblebee-specific strains of honey bee viruses occurred, as expected if spillover led to a true host expansion involving bumblebee-bumblebee transmission. Honey bee viruses, namely deformed wing virus, black queen cell virus, and sacbrood virus, which were present in the bumblebees did not show evidence of diversification among hosts, suggesting environmental exposure or dead-end spillover, rather than spillover host expansion.